Analisis Common Size Untuk Menilai Kinerja Keuangan Perusahaan Pada Perusahaan Manufaktur Sub Sektor Pakan Ternak yang Terdaftar Di Bursa Efek Indonesia Periode 2019 - Nila Astria (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
The aim of this research is to measure the financial performance based on financial reports of a company by using Common Size analysis. The financial reports used were every account in the balance sheet and income statement. The financial reports discussed the animal feed sub-sector manufacturing companies listed in Indonesian Stock Exchange for the period of 2019. There were four companies used in this research, namely PT Charoen Pokphand Tbk, PT Japfa Comfeed Indonesia Tbk, PT Malindo Feedmill Tbk, dan PT Sierad Produce Tbk. The results of this research showed that almost all animal feed companies had poor financial performance in 2019. PT Sierad Produce Tbk was the only animal feed company that had good financial performance compared to the other three animal feed companies. This was caused by the decrease in the percentage of current assets so that it affected the rate of the increase in company’s profits. With this the company is expected to make debt management and be able to manage the cost of expenses incurred during the production process.